On the validity of data produced by isolated and synthesized contingencies during the functional analysis of problem behavior. Issue 3 (28th October 2020) - Tiger, Jeffrey H.; Effertz, Hannah M.
Abstract : Functional analyses are intended to identify the reinforcers maintaining problem behavior in order to inform clinicians' selection of interventions. Traditionally, these analyses have exposed problem behavior to multiple, isolated reinforcement contingencies and in doing so, have ruled in and ruled out potential sources of reinforcement. Recently, some functional analysis models have forgone testing individual reinforcement contingencies and instead exposed problem behavior to 2 or more reinforcers simultaneously in a single, synthesized reinforcement contingency. The current review applies assessment analytics to these approaches to consider their relative sensitivity, specificity, discriminant validity, and predictive validity to yield practice recommendations and to nominate areas of future research.